1987
DOI: 10.1177/002221948702001007
|View full text |Cite
|
Sign up to set email alerts
|

The Continuous Performance Test in Learning Disabled and Nondisabled Children

Abstract: The performance of 30 learning disabled (LD) children with specific memory disability was compared to 30 matched controls on a computerized test of attentional skills. The Continuous Performance Test (CPT) provided a measure of omission errors, commission errors, and average rate of responding to a color-letter combination target. TheLD group showed more omission errors and a slower rate of responding but did not differ from controls on commission errors. The results were interpreted from a signal detection pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
0
29
0
2
Order By: Relevance
“…Meta-analyses of studies using the CPT revealed that omission errors (lack of response to target stimuli) and commission errors (responses to nontarget stimuli) are medication-sensitive, as indicated by a decreased number of both omission and commission errors of children with ADHD receiving MPH. Omission and commission errors are assumed to reflect inattention and impulsivity, respectively (Barkley 1991;Corkum and Siegel 1993;Eliason and Richman 1987;Epstein et al 1998;Halperin et al 1991;Lassiter et al 1994). Furthermore, reaction time and the variability of reaction time have been found to decrease following MPH administration (Losier et al 1996;Riccio et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of studies using the CPT revealed that omission errors (lack of response to target stimuli) and commission errors (responses to nontarget stimuli) are medication-sensitive, as indicated by a decreased number of both omission and commission errors of children with ADHD receiving MPH. Omission and commission errors are assumed to reflect inattention and impulsivity, respectively (Barkley 1991;Corkum and Siegel 1993;Eliason and Richman 1987;Epstein et al 1998;Halperin et al 1991;Lassiter et al 1994). Furthermore, reaction time and the variability of reaction time have been found to decrease following MPH administration (Losier et al 1996;Riccio et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies involving clinical controls indicate that continuous performance tests do not reliably distinguish children with ADHD from other clinical groups (Barkley, DuPaul, & McMurray, 1990;Corkum & Siegel, 1993;Koriath, Gualtieri, Van Bourgondien, Quade, & Werry, 1985). In addition, children with RD tend to perform poorly on continuous performance tests (Eliason & Richman, 1987;Tarnowski, Prinz, & Nay, 1986). Two DD studies have used the commercially available Conners' Continuous Performance Test (CCPT;Conners, 1995).…”
mentioning
confidence: 99%
“…Deficits in vigilance task performance have been demonstrated for a variety of groups of children with information processing or attentional difficulties. For example, children at risk for schizophrenia (Nuechterlein, 1983;Rutschmann, Cornblatt, & Erlenmeyer-Kimling, 1977), hypoxic children (O'Dougherty et al, 1984), learningdisabled children (Dainer et al, 1981;Eliason & Richman, 1987;Tarnowski, Prinz, & Nay, 1986), and educationally handicapped students (Keogh & Margolis, 1976) all have poor performance on these tasks. However, attempts to define disorder-specific deficits have not yielded a consistent pattern (Nuechterlein, 1983;O'Dougherty et al, 1984;Tarnowski et al, 1986).…”
mentioning
confidence: 99%